2014
DOI: 10.1111/jne.12128
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Effects of Kainic Acid on Vasopressin‐Enhanced Green Fluorescent Protein and Oxytocin‐Monomeric Red Fluorescent Protein 1 Neurones Isolated from the Supraoptic Nucleus in Transgenic Rats

Abstract: The supraoptic nucleus (SON) contains two types of magnocellular neurosecretory cells: arginine vasopressin (AVP)-producing and oxytocin (OXT)-producing cells. We recently generated and characterised two transgenic rat lines: one expressing an AVP-enhanced green fluorescent protein (eGFP) and the other expressing an OXT-monomeric red fluorescent protein 1 (mRFP1). These transgenic rats enable the visualisation of AVP or OXT neurones in the SON. In the present study, we compared the electrophysiological respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Our present studies in acute slices and organotypic cultures constitute an initial effort to decrypt some structure-function relationships in the magnocellular neuroendocrine circuits, complementing current efforts to decipher the electrical behavior of hypothalamic neuroendocrine cells (Osterstock et al, 2010 ; Murphy et al, 2012 ; MacGregor and Leng, 2013 ; Wamsteeker Cusulin et al, 2013 ; Ohkubo et al, 2014 ; Briffaud et al, 2015 ; Iremonger and Herbison, 2015 ; Royo et al, 2015 ). Although, this ideally at some point requires analysis and manipulations of the neuroendocrine networks in vivo (Campos and Herbison, 2014 ), a wealth of ex vivo studies should also continue to provide irreplaceable information.…”
Section: Discussionmentioning
confidence: 73%
“…Our present studies in acute slices and organotypic cultures constitute an initial effort to decrypt some structure-function relationships in the magnocellular neuroendocrine circuits, complementing current efforts to decipher the electrical behavior of hypothalamic neuroendocrine cells (Osterstock et al, 2010 ; Murphy et al, 2012 ; MacGregor and Leng, 2013 ; Wamsteeker Cusulin et al, 2013 ; Ohkubo et al, 2014 ; Briffaud et al, 2015 ; Iremonger and Herbison, 2015 ; Royo et al, 2015 ). Although, this ideally at some point requires analysis and manipulations of the neuroendocrine networks in vivo (Campos and Herbison, 2014 ), a wealth of ex vivo studies should also continue to provide irreplaceable information.…”
Section: Discussionmentioning
confidence: 73%
“…OXT is mainly produced in neurosecretory neurons located in the SON and PVN in the hypothalamus. We successfully generated transgenic rats bearing an OXT-mRFP1 fusion gene, which resulted in the visualization of OXT expression 19,20,[25][26][27][28] . The PVN is divided into regions such as apPVN, dpPVN, and mPVN, and previous studies with the OXT-mRFP1 transgenic rats reported different effects 29 .…”
Section: Discussionmentioning
confidence: 99%
“…1B). AVP-eGFP Tg rats provide a unique model for visualizing the molecular dynamics of AVP in vivo and for live imaging and/or electrophysiology of identified AVP neurons without any specific histological labeling [13][14][15][16][17][18][19][20]. Previous studies have demonstrated that the exposure of AVP-eGFP Tg rats to dehydration induced significantly greater expression of GFP in PVN and SON neurons, mirroring that of native AVP [8,9].…”
Section: Introductionmentioning
confidence: 99%